2012
DOI: 10.5152/balkanmedj.2011.007
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Melanocortin-1 Receptor (Mc1R) Gene in Vitiligo

Abstract: Objective: Vitiligo is a progressive skin pigmentation disorder, which may be acquired or hereditary, frequently seen, and may influence every age group. The melanocortin 1 receptor (MC1R) gene is a major determinant of human pigmentation. In our study, polymorphic differences of the MC1R gene at the DNA level has been investigated in patients with vitiligo. Materials and Methods:In our study, polymorphic differences of the MC1R gene at the DNA level has been investigated in vitiligo 60 patients, whose familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…distribution of V60L shows that this allele is circumscribed to Europe and the Near East (Gerstenblith et al, 2007;Acar, Bozkurt and Görgülü, 2012;Galore-Haskel et al, 2009;Eskandani et al, 2010). However, we show that this increase in fitness for the population has collateral damaging consequences for the individual´s health.…”
Section: Discussionmentioning
confidence: 99%
“…distribution of V60L shows that this allele is circumscribed to Europe and the Near East (Gerstenblith et al, 2007;Acar, Bozkurt and Görgülü, 2012;Galore-Haskel et al, 2009;Eskandani et al, 2010). However, we show that this increase in fitness for the population has collateral damaging consequences for the individual´s health.…”
Section: Discussionmentioning
confidence: 99%
“…These negative correlations may represent a compensatory mechanism trying to correct the defective pigmentation. Some authors have reported that certain alleles of the MC1R gene might be protective against vitiligo, while others have found no significant relation between MC1R gene polymorphisms and vitiligo . On the other hand, a genome‐wide association analyses reported an association between the MC1R locus and generalised vitiligo …”
Section: Discussionmentioning
confidence: 99%
“…Most vitiligo susceptibility loci encode melanocyte components, and antioxidant and immune-regulatory proteins [40,246]. For example, associations have been established between vitiligo pathogenesis and polymorphisms in tyrosinase (TYR) [247], catalase (CAT) [65], glutathione peroxidase (GPX) [65], melanocortin 1 receptor (MC1R) [248], major histocompatibility complex (MHC) [249], NACHT leucine-rich repeat protein 1 (NLRP1) [172] [252]. Both protective and susceptibility-increasing effects have been found in the case of different polymorphisms in these genes [253,254].…”
Section: Cross Talk Between Oxidative Stress Er Stress and Immune Symentioning
confidence: 99%